Analysis of fresh water ornamental fish production (Goldfish, Koi and Betta Fish) in Tulungagung district, East Java, Indonesia - Miftachul Andriyan Afnan; Ganjar Adhywirawan Sutarjo; Hariyadi Hariyadi (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
Freshwater ornamental fish such as carp, koi, and betta fish is a kind of a very potential happy developed in the Tulungagung district. The total production in the last 3 years is still above the average production of other freshwater ornamental fish. This study aims to know the best influence on the production of freshwater ornamental fish by the influence of capital, cultivation pond, manpower, and technology. The method of research used is by the purposive sampling method of predetermined culture. Furthermore, the data that has been in can be inserted into SPSS 18 which is in multiple linear regression. The results of this research show that on the cultivation of goldfish, the production factor has a significant effect on the production and the technology variable has the highest beta coefficient of 0.364. For the cultivation of Koi fish, the production factor does not have a significant influence on the production, and the technology variable has the highest beta coefficient of 0.462. For betta fish farming, production factors have no significant effect on production variable and capital variables have the highest beta coefficient of 0.353 which means that production variables are heavily influenced by modal variables. Based on the results of the research can be concluded that out of all production factors, technology has the most influential likelihood on the marketing of freshwater ornamental fish.